PG69 Our virtual and face to face world: training for simulated patients. (10th November 2020) - Thame, Anna; Hamilton, Carrie; Booth, Jane
Abstract : Background: The ASPiH standards 1 state that 'a variety of simulation modalities, including simulated patients (SPs) are incorporated to create appropriate realism and achieve the objectives of the session' (standard 15). The standards state that faculty are fully trained in debriefing (standard 3); of which SPs are a part. Our educational Academy provides SPs to around twenty universities and healthcare organisations, therefore, ongoing, meaningful, and robust training for SPs is paramount. Lacklustre, opportunistic and 'learning on the job' involvement of SPs is unsafe and unethical, for educators and for SPs. Summary of Work: A comprehensive 45 minute training film was created collaboratively with SPs (with a range of experience) and educators. The aim of the online training was to provide thorough training on all aspects of SP activity. The learning outcomes for the training include, having an understanding/awareness of: the expectations of SPs professionalism respectfulness and inclusivity different forms of simulations, situations, and roles approaching strong emotions (such as anger and grief) and managing appropriately role preparation and authenticity delivering feedback to participants appropriately and objectively effective de–role post simulation Demonstrations by SPs and educators of fishbowl simulation, forum theatre, learner participation and delivering feedback are narrated and embedded within the learning. Summary of Results: The training film was distributed to 130 SPs; it provides self-directed learning as a refresher to experienced SPs and as essential training to all new SPs. Those undertaking the training are logged, including feedback with an open channel for 'Q&A'. Self-assessment, feedback from SPs and peer observation indicate that the learning outcomes of the training have been met providing the Academy with important quality assurance markers and demonstrating further alignment with the ASPiH standards, which state that 'a review of SPs occurs'. Discussion and Recommendations : The original aim of the training has been achieved, high calibre SP provision. There have been unanticipated repercussions, one being that the training has been incorporated into our faculty 'Train the Trainer in Working with SPs' (online and face-to-face) supporting the ASPiH standard: 'Training is provided to all faculty to engage with SPs' (standard 18). Additionally, online training (as a result of COVID-19) are valuable learning resources, with this training impacting the plethora of organisations we work with. It ultimately affects healthcare professionals' skills in delivering kind, safe, empathetic patient care. Reference: Simulation-Based Education in Healthcare. Standards Framework and Guidance. Association for simulated practice in healthcare (ASPiH) standards for simulation-based education. 2016 http://aspih.org.uk/wp-content/uploads/2017/07/standards-framework.pdf